2014
DOI: 10.1159/000357754
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Striatal and Pallidal Regions in the Subpallium of Anamniotes

Abstract: The telencephalic basal ganglia (BG) of amniotes consist of two subdivisions, striatum and pallidum, which share many features, including development, cell types, neurotransmitter organization and hodology. In particular, these two subdivisions during development are defined on the basis of discrete gene expression patterns (genoarchitecture or genoarchitectonics). The characterization of the BG in the subpallium of representatives of the different classes of anamniote vertebrates was first approached in studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 41 publications
7
87
1
Order By: Relevance
“…In particular, the pallidal division, which contains neurons of Nkx2.1 and/or Lhx6 lineage ( table 1 ; fig. 2 ) [Mueller et al, 2008;González and Northcutt, 2009;Mueller and Wullimann, 2009;Quintana-Urzainqui et al, 2012], appears to receive ENK+ and SP+ input from the striatum and also contains LANT6+ cells Northcutt, 1987, 1992; reviewed by González et al, 2014]. Importantly, data on Nkx2.1 expression in lungfishes and cartilaginous fishes have revealed that the pallidal subdivision is smaller (more medially restricted) than previously thought [González and Northcutt, 2009;Quintana-Urzainqui et al, 2012].…”
Section: Fishesmentioning
confidence: 98%
See 2 more Smart Citations
“…In particular, the pallidal division, which contains neurons of Nkx2.1 and/or Lhx6 lineage ( table 1 ; fig. 2 ) [Mueller et al, 2008;González and Northcutt, 2009;Mueller and Wullimann, 2009;Quintana-Urzainqui et al, 2012], appears to receive ENK+ and SP+ input from the striatum and also contains LANT6+ cells Northcutt, 1987, 1992; reviewed by González et al, 2014]. Importantly, data on Nkx2.1 expression in lungfishes and cartilaginous fishes have revealed that the pallidal subdivision is smaller (more medially restricted) than previously thought [González and Northcutt, 2009;Quintana-Urzainqui et al, 2012].…”
Section: Fishesmentioning
confidence: 98%
“…Developmental, neurochemical and connectivity data show that the basal ganglia contain two major subdivisions in all jawed vertebrates studied: an input station called striatum and an output station called pallidum (see reviews by Marín et al [1998]; Reiner et al [1998]; Medina [2009] and González et al [2014]), and recent data in lobe-finned fishes (e.g. lungfishes) [González and Northcutt, 2009], ray-finned fishes (e.g.…”
Section: Striatum Versus Pallidum: Were They Present In the First Vermentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been especially valuable for the telencephalon with its great variability in morphology between vertebrate species and has led to the clarification of the homology within subdivisions of the telencephalon between different vertebrate species, such as the domestic mouse, the chicken and the African clawed frog (e.g. 722 ). For example, the gene expression of Tbr1 and Eomes ( Tbr2 ) has been successfully used to identify the extent of the pallium in tetrapod embryos 9, 21, 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Within the anuran forebrain, the striatum (anterior) is continuous with the central and medial amygdala (posterior), and clearly separated from the dorsal/ventral pallidum and the BST and septum (19). An important discovery during the study of the embryological development of anuran basal ganglia was the finding that the BST and part of the septum are also of pallidal instead of striatal origin (23,24). This is interesting because the BST is a suitable structure to execute the limbic component of lamprey GPh.…”
Section: The First Land Animalsmentioning
confidence: 99%